Successful management of atonic uterus in a caesarean section with modified B–Lynch sutures: a case report - Wadhwa, Eshita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Postpartum haemorrhage (PPH) still remains one of the primary causes of maternal mortality throughout the planet. Prompt management of PPH with medical and surgical intervention should be encouraged as it can be lifesaving. Primary methods of management include a simple bi-manual compression, oxytocic drugs such as oxytocin, ergometrine, and prostaglandins these are safe and effective, but can occasionally prove inadequate or unsatisfactory following which a trial of tamponade should be given if still unsuccessful uterine compression sutures running through the full thickness of both anterior and posterior walls of the uterus are taken which cause mechanical compression and hence control the excessive blood loss. In this study, we report a case of atonic uterus in a case of abruption managed with B-lynch sutures.